Bio-waste enriched vermicompost effects on productivity and nutrient uptake of soybean (Glycine max) and succeeding wheat (Triticum aestivum) - Arun Kumar Shukla; H.S. Kushwaha; S. K. Choudhary; Vinod Kumar Tiwari (Annals of Agricultural Research, 2023)
The field trial were conducted at Krishi Vigyan Kendra, Kasturbagram, Indore, Madhya Pradesh during 2017-18 and 2018-19 to study the effect of bio-waste enriched vermicompost (VC) on productivity and nutrients uptake of soybean and succeeding wheat. Result showed that amongest the bio-waste treatments, the farm waste enriched VC at the rate of 2 t/ha increased significantly the grain yield, straw yield and total biomass production of soybean. The total N uptake of soybean was recorded significantly superior and P and K uptake had noted markedly higher under farm waste enriched VC treatment. The residual effect of biowaste enriched VC also gave significantly more grain and straw yield and total biomass production of wheat. This treatment also noted significant greater N uptake and conspicuously more P and K uptake by wheat. In case of additive treatments, the vermicompost enriched with all the three additives (rock phosphate + PSB + Trichoderma) recorded maximum productivity and total NPK uptake by grain and straw of soybean. In case of wheat, the grain and straw yield, total biomass and total NPK uptake of wheat was found higher under RP + PSB + Trichoderma.